Carbon Footprint Analysis Of Food Waste From Restaurants In Bogor City - Fernandez, Yohana Bharagita; Ardiatma, Dodit; Ilyas, Nurilman (Jurnal Info Sains : Informatika dan Sains, 2024)
Restaurants are Indonesia's biggest producers of trash since they provide meals every day, which contributes to a rise in food waste. The purpose of this study was to examine the quantity and kind of food waste produced by large-scale restaurants in Bogor City, as well as the carbon footprint that this garbage leaves behind. Additional evaluation of the impact of food waste output and composition on CO2 emissions was done in this study. This study separates edible food waste from non-edible food waste using a sample technique based on Waste Composition Analysis (WCA). The emission factor is calculated in order to determine the carbon footprint. According to the study's findings, which included 120 samples from three restaurants in Bogor City, the average daily production of food waste from the simple payakumbuh, pagi sore, and bumi aki restaurants in Bogor City was 4,239.70 g/plate, and the average daily generation of edible food waste was 12,026.70 g/org. It is made up of 14.3% foods high in protein, 40.1% fruits and vegetables, and 45.6% foods high in carbohydrates. Produce (40.1%): fruits and vegetables; foods high in protein (14.3%). Pagi Sore generates the least amount of edible food waste (988 g/org/day), whereas Payakumbuh restaurant produces the most (26,834 g/org/day).